Spanish broom (Spartium junceum L.) - feedstock for bioplastic and bioenergy industry - Kovačević, Zorana, tekstilna tehnologinja; Jurišić, Vanja; Grubor, Mateja; Matin, Ana; Krička, Tajana; Bischof-Vukušić, Sandra (2019)
Spanish Broom (Spartium junceum L.) is a Mediterranean plant of various usage possibilities. Its fibres were known since ancient time but in some point of last century, more accurately in 1950s, their production was abandoned due to the negative economic effect. Another drawback was large time consumption, especially during the old tradition method – Spanish Broom maceration in salt water. Nowadays, due to technology development and ecological awareness, it is much easier to produce Spanish Broom fibres of enhanced quality. One of the fibre extraction methods is the one assisted with microwave oven. Demerit of such fibre production is in large residue content after obtaining fibres - approx. 90 % of initial Spanish Broom weight. Due to the need for finding sustainable solutions in the development of new materials, the usage of Spanish Broom fibres in the service of reinforcement for biopolymer poly (lactic acid) (PLA) matrix was investigated. Obtained results target our further research into the direction of Spanish Broom fibres and PLA application in the production of green composites. The aim of this research was to prove that developed product can be categorized under the biodegradable group by investigating its degradation properties using serine endopeptidase enzyme. The results show positive degradation effect while using 50 wt.% (on weight of material) enzyme concentration during a 5-day treatment. Stem residues of Spanish Broom plant derived from salty water and microwave maceration were further investigated for their potential as raw material for second-generation biofuel production. Examination of its energy properties consisted of determination of proximate and ultimate properties of the biomass. The results show low moisture content (6.5 % - 7.5 %), ash content below 5 % and higher values of fixed carbon and volatile matter content of 13.2 % and 75 %, respectively.
Bibliografija: 25 jed.
Abstract.
Keywords: Spartium junceum L. -- Brnistra -- Biomasa -- Biogorivo -- Biorazgradnja